Can menu labeling affect away-from-home-dietary choices? - Castellari, Elena; Marette, Stéphan; Moro, Daniele; Sckokai, Paolo (Bio-based and Applied Economics, 2019)
This study aims to evaluate the impact of two menu-labeling formats on changes in dietary choices in an away-from-home meal, specifically in a university cafeteria. A field experiment at a university cafeteria in Italy was conducted providing two different types of nutritional labels. The experiment lasted four days, spread over two weeks during which a total of 930 observations were collected. During each day of the experiment, only in one food line (treated line) a label indicating the healthy options was displayed, while in the other line no label was presented (control line). The paper describes two indexes to measure how the selected food choices for each participant are in line with what suggested by the labels. We define five different classes of these indexes and we test our hypothesis using an ordered logit model. Results show the labels we provided had no significant impact on changing the tray composition, in accordance with other previous experiments suggesting that adding only nutritional information in a restaurant setting does not necessarily encourage healthier choices. The paper concludes highlighting the need of a multifaceted approach to design effective public policies enhancing healthier choices in a self-service restaurant. Specifically, the provision of nutritional information by itself can have zero or low impact unless it synergizes with others instruments such as nutritional education, social norm provision and nudges. In the conclusions, some suggestions on public policies addressing the promotion of healthy food habits are given.